Therapeutic activities for children and teens coping with health issues - Hart, Robyn; Rollins, Judy, 1943- (Hoboken, N.J. : John Wiley & Sons, 2010)
'Building on children's natural inclinations to pretend and reenact, play therapy is widely used in the treatment of psychological problems in childhood. This book is the only one of its kind with more than 200 therapeutic activities specifically designed for working with children and teenagers within the healthcare system. It provides evidence-based, age-appropriate activities for interventions that promote coping. The activities target topics such as separation anxiety, self-esteem issues, body image, death, isolation, and pain. Mental health practitioners will appreciate its'cookbook' format, with quickly read and implemented activities.'--Provided by publisher.
Machine generated contents note: Chapter 1: Separation and Stranger Anxiety -- Chapter 2: Self-Expression -- Chapter 3: Self-Esteem -- Chapter 4: Body Image -- Chapter 5: Group Interaction and Socialization -- Chapter 6: Desensitization to Medical Implements -- Chapter 7: Tension Release -- Chapter 8: Humor -- Chapter 9: Death and Bereavement -- Chapter 10: Culture -- Chapter 11: Isolation and Immobilization -- Chapter 12: Pain -- Chapter 13: Breathing -- Chapter 14: Teaching -- Chapter 15: Activities of Daily Living -- Chapter 16: Perceptual Motor -- Appendix A: Art Materials and Projects for Children and Other High-Risk Individuals -- Appendix B: Web Sites.
Book is accopanied by one CD/diskette, entitled' Therapeutic activities for children and teens coping with health issues' bearing the same call number and available at Bahagian Koleksi Media.
Includes bibliographical references and index.
Keywords: Play therapy; Child psychotherapy; Adolescent psychotherapy; Patients -- psychology; Child psychology; Play Therapy -- methods; Adolescent psychology; Mental disorders -- Therapy; Patients -- psychology